Peter Gregory. The myth of market failure : employment and the labor market in Mexico. Baltimore ; Londres : The Johns Hopkins University Press, 1986. (Publicado para el Banco Mundial) - García, Brígida (Estudios Demográficos y Urbanos, 1988)
PETER GREGORY. The Myth of Market Failure. Employment and the labor Market in México. Baltimore y Londres, The Johns Hopkins University Press (publicado para el Banco Mundial), 1986.